Inheritance of persistent foramen ovale and atrial septal defects and the relation to familial migraine with aura. Issue 11 (14th October 2004) - Wilmshurst, P T; Pearson, M J; Nightingale, S; Walsh, K P; Morrison, W L
Abstract : Objective: To determine whether smaller atrial shunts (large persistent foramen ovale (PFO) and small atrial septal defect (ASD)) are inherited and whether this has a role in the inheritance of migraine with aura. Methods: Contrast echocardiography was used to detect atrial shunts in 71 relatives of 20 probands with a significantly sized atrial shunt (large PFO or ASD). Four families with three generations, 14 families with two generations, and two sibships were studied. The contrast echocardiograms were performed blind to history of migraine. A consultant neurologist, who was blinded to cardiac findings, categorised migraine symptoms in subjects. Results: The occurrence of atrial shunts was consistent with autosomal dominant inheritance. Usually shunts were large PFOs, but in some cases they were ASDs. There was also evidence that inheritance of more complex congenital heart disease may be related to the inheritance of PFOs. When the proband had migraine with aura and an atrial shunt, 15 of the 21(71.4%) first degree relatives with a significant right to left shunt also had migraine with aura compared with three of 14 (21.4%) without a significant shunt (p < 0.02). Conclusions: There is dominant inheritance of atrial shunts. This is linked to inheritance of migraine with aura in some families.